Improving Summative Evaluation of Clerkship for Health Services Management Students in Tabriz Faculty of Health and Nutrition, Using OSFE - JS Tabrizi; A Jannati; Z Hamzehei; MR Narimani (Tehran University of Medical Sciences, 2010)
Background: Education and evaluation should be designed to educate and evaluate students in the real field or similar to their future work place. This study aimed to improve summative evaluation in internship. Material & Methods: A quantitative (61 students) and qualitative (15 students) study with health services management students conducted in Tabriz Faculty of Health and Nutrition. OSFE was developed as a summative evaluation method based on students' experiences about final evaluation of clerkship, which ascertained using two FGDs. In the OSFE method students attended in the several stations to do particular skills individually. In each station students' skill has been assessed by a trained examiner using standard checklists. At the end of exam, students' opinion about new method has been asked through qualitative and quantitative methods. Qualitative data analyzed by hand and SPSS software was used to analyze quantitative data. Results: Findings from FGDs (after OSFE) showed that the majority of students were satisfied about OSFE and they believed that it is a good method to assess students' skills and competencies. Quantitative study also demonstrated that 74% of students believed that OSFE is a good method to evaluate their capabilities and 70% verified that they have been attended in an orientation session about OSFE. Moreover, 58% considered OSFE as an equitable method. Conclusion: It can be suggested that OSFE could be used as a valuable summative evaluation method for non-medical students' clerkship and practical courses.